Associations between fine particulate matter and in-home blood pressure during the 2022 wildfire season in Western Montana, USA - Ethan S Walker; Taylor Stewart; Rajesh Vedanthan; Daniel B Spoon (Environmental Research: Health)
Wildfires continue to increase in size, intensity, and duration. There is growing evidence that wildfire smoke adversely impacts clinical outcomes; however, few studies have assessed the impact of wildfires on household air quality and subclinical cardiovascular health indicators. We measured continuous indoor and outdoor fine particulate matter (PM _2.5 ) concentrations from July–October 2022 at 20 residences in the rural, mountainous state of Montana in the United States. We used a combination of satellite-derived smoke plume data from the National Oceanic and Atmospheric Administration’s Hazard Mapping System and household-level daily mean PM _2.5 concentrations to classify wildfire-impacted days. One participant from each household self-reported in-home blood pressure (BP) on weekly electronic surveys. We used linear mixed-effects regression models to assess associations between air pollution exposures (PM _2.5 concentrations; number of wildfire-impacted days) and systolic BP (SBP) and diastolic BP (DBP). Models were adjusted for potential time-variant confounders including temperature, humidity, and self-reported exercise. Compared to survey periods with 0 wildfire days, SBP was 3.83 mmHg higher (95% Confidence Interval [95% CI]: 0.22, 7.44) and DBP was 2.36 mmHg higher (95% CI: −0.06, 4.78) during periods with 4+ wildfire days. Across the entire study period, a 10 µ g m ^−3 increase in indoor PM _2.5 was associated with 1.34 mmHg higher SBP (95%CI: 0.39, 2.29) and 0.71 mmHg higher DBP (95% CI: 0.07, 1.35). We observed that wildfire-impacted days and increasing household-level PM _2.5 concentrations are associated with higher in-home BP. Our results support growing literature which indicates that wildfires adversely impact subclinical cardiovascular health. Clinical and public health messaging should emphasize the cardiovascular health impacts of wildfire smoke and educate on exposure-reduction strategies such as indoor air filtration.